2010
DOI: 10.4248/ijos10025
|View full text |Cite
|
Sign up to set email alerts
|

Association between Diabetes Mellitus and Oral Health Status in Japanese Adults

Abstract: Aim The objective of this study was to analyze the oral health among Japanese adults, with and without diabetes mellitus. MethodologyThe subjects were 518 community residents aged 20 to 91 years in Japan, who participated in the "Akita health and nutrition survey" and the "Akita dental disease survey", conducted in 2006. The surveys comprised a self-administered questionnaire, along with medical and dental examinations.Results Using the community periodontal index (CPI), the mean numbers of sextants presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
6
0
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
4
6
0
2
Order By: Relevance
“…CHD subjects with diabetes and smoking having missing teeth were five times higher in number and two times higher with a mean tooth loss than the healthy subjects. These results support the previous studies [22,23] showing that smoking and diabetes significantly contribute to tooth loss. However, cardiac patients of this study remained 1.232 times at higher risk for tooth loss, and this association was observed independent of confounding factors.…”
Section: Discussionsupporting
confidence: 95%
“…CHD subjects with diabetes and smoking having missing teeth were five times higher in number and two times higher with a mean tooth loss than the healthy subjects. These results support the previous studies [22,23] showing that smoking and diabetes significantly contribute to tooth loss. However, cardiac patients of this study remained 1.232 times at higher risk for tooth loss, and this association was observed independent of confounding factors.…”
Section: Discussionsupporting
confidence: 95%
“…Another study by Macek and Tomar (2009) indicated that dental care visits for adults with diabetes were unrelated to their periodontal health (Macek & Tomar, 2009). However, the findings reported here are similar to the Ueno et al (2010) study in that periodontal disease as measured by the number of natural teeth is influenced, to some degree, by diabetes status (Ueno et al, 2010). Differences in outcomes may also occur due to respondent characteristics (i.e., race, gender, poverty status, and age) and measurement of diabetes status.…”
Section: Discussionsupporting
confidence: 88%
“…3,7 Essa doença pode ser classificada mais comumente como tipo 1 e tipo 2. 3,7,12,14,15,16 O DM tipo 1, anteriormente conhecido como insulinodependente, diabetes juvenil, afeta cerca de 5% a 10% de todos os pacientes diabéticos e ocorre mais comumente em crianças e adultos jovens. 7 É um estado de deficiência de insulina devido a uma disfunção imune onde as células reativas dirigidas para as células beta são produzidas e proliferam, resultando na destruição destas, dentro das ilhotas de Langerhans do pâncreas.…”
Section: Revisão Da Literaturaunclassified
“…5 Diabetes e cavidade oral Na cavidade oral, a hiperglicemia leva ao aumento dos níveis de glicose do fluido gengival crevicular. 16 A hiperglicemia também afeta a fagocitose, quimiotaxia e adesão de leucócitos polimorfonucleares. Estes e outros mecanismos patogênicos subjazem a complicação oral de DM.…”
Section: Revisão Da Literaturaunclassified